2020
DOI: 10.3389/fneur.2020.00356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low Diastolic Blood Pressure to Cardiovascular Risk in Patients With Ischemic Stroke or Transient Ischemic Attacks Under Different Systolic Blood Pressure Levels

Abstract: Background: In the context of recently updated strategies of pressure management, there is a paucity of evidence on the effect of diastolic blood pressure (DBP) level on adverse events among stroke patients. This study aimed to examine the effect of low DBP (<60 mmHg) under different levels of systolic blood pressure (SBP) on the risk of composite events and stroke recurrence among patients with ischemic stroke (IS) or transient ischemic attack (TIA).Material and Methods: This study was conducted in 2,325 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Conversely, several earlier studies suggested that lower DBP or intensive DBP reduction may increase the risk of coronary artery disease (23,24). A recent study further suggests that low DBP (<60 mmHg) was associated with an increased risk of composite events among patients aged 20 years or older, with ischemic stroke or transient ischemic attack (25). In a population of veterans aged 45 or older, reduction of DBP below 70 mmHg was associated with increased all-cause mortality (26).…”
Section: The Optimal Pp May Vary Between Ages and Sexesmentioning
confidence: 99%
“…Conversely, several earlier studies suggested that lower DBP or intensive DBP reduction may increase the risk of coronary artery disease (23,24). A recent study further suggests that low DBP (<60 mmHg) was associated with an increased risk of composite events among patients aged 20 years or older, with ischemic stroke or transient ischemic attack (25). In a population of veterans aged 45 or older, reduction of DBP below 70 mmHg was associated with increased all-cause mortality (26).…”
Section: The Optimal Pp May Vary Between Ages and Sexesmentioning
confidence: 99%
“…However, the study failed to find an analogical trend for stroke recurrence. 23 In our study, patients who died had significantly lower DBP than patients who survived.…”
Section: Discussionmentioning
confidence: 44%
“…Although the KDIGO guideline does not stipulate a diastolic target, in attempting to lower SBP <120 mm Hg in patients with CKD, there is also the risk of driving diastolic BP too low especially in older patients, who often have low diastolic BP because of advanced atherosclerosis. 27 Diastolic BP is important for adequate coronary artery filling. Many studies have demonstrated that low diastolic BP <70 mm Hg is associated with higher risk of CVD, recurrent CV events, and stroke compared with diastolic BP between 71 and 89 mm Hg.…”
Section: Potential Hazards Of Driving Diastolic Bp Too Lowmentioning
confidence: 99%
“…Many studies have demonstrated that low diastolic BP <70 mm Hg is associated with higher risk of CVD, recurrent CV events, and stroke compared with diastolic BP between 71 and 89 mm Hg. [27][28][29][30] People with CKD already have a high risk of CVD. 4 The practice points of the KDIGO guideline in relation to the target BP recommendation highlight the potential hazards associated with the low BP target and suggest that clinicians can reasonably offer less intensive BP lowering therapy in those with symptomatic postural hypotension.…”
Section: Potential Hazards Of Driving Diastolic Bp Too Lowmentioning
confidence: 99%
See 1 more Smart Citation